SIGNIFIKANSI TANPA ALAS KAKI: SUATU PERSPEKTIF LAIN SEHUBUNGAN DENGAN MENANGGALKAN KASUT MUSA DARI KAKINYA DI TEMPAT KUDUS - Alfonso Tarigan (Jurnal Koinonia, 2015)
The significance of removing Moses’ sandals from his feet has beenunderstood differently. First, it is to signify an act of respect and politeness. Secondis to denote an act of keeping cleanliness or purity. This paper does not discuss thedifferent opinions nor give a comprehensive answer to the significance of the action.Instead, it tries to look the performance based on some other possible lights.The lights from studying the text, context, and its relations to Passover, Sinai,and sanctuary services show that Moses’ act at the mount of Horeb contains moralpurpose. God wants Moses to depend on Him fully in order he can be successful indoing the appointed task from God, that is, to deliver the Israelites from theEgyptian’s bondage. This is to implies that the same principle prevail upon us todayin order to be successful doing God’s work.